Aromaticity of biphenylene networks; Physical Chemistry Chemical Physics; Vol. 26, iss. 39 - Valiulina L. I. Lenara; Valiev R. R. Rashid Rinatovich; Cherepanov V. N. Victor; Stepanova E. V. Elena Vladimirovna (2024, 2024)
Title screen